(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article describes the specifics of social-pedagogical work with parents in difficult life circumstances. The author analyzes models, technologies and methods of providing assistance to families in difficult life circumstances. There provided basic components of social- pedagogical work with parents on the basis of socio-psychological rehabilitation center. There also stressed the priority of the comprehensive assessment of the child’s needs in the rehabilitation process. The author emphasize the nessesity of the comprehensive approach and multidisciplinary team work (services for children, centers for social and psychological rehabilitation of children, centers of social services for family, children and youth) in helping process.